Urban land reforms for equitable infrastructure - Pandey, K.K. (2011)
The formal supply of land and strategic use of land in urban areas hold the key to improve infrastructure services to poor. Basic Services for Urban Poor (BSUP) programme of Government of India in this regard provides a model from concept to practice. The seven point charter covering secure tenure, affordable housing, water, sanitation, health and social security gives a line of action based on using land as an instrument. This includes vertical supply, self help, incremental development, combination of commercial use, etc. to build infrastructure and services in a sustainable manner. While examining the national policies and programmes it is noted that besides the implementation of Central schemes, the follow-up has been encouraging and several initiatives have emerged at state and city level. These include states of Gujarat, Rajasthan, Maharashtra, Andhra Pradesh and so on. Many cities such as Mumbai, Pune, Nagpur, Jaipur, etc., are also showing successful models for wider application. The policy intervention and programmes initiated by Government of India in recent past covering National Urban Housing and Habitat Policy (NUHHP), 2007, Affordable Housing in Partnership, (AHP) Interest Subsidy for Housing Urban Poor (ISHUP), Jawaharlal Nehru National Urban Renewal Mission (JNNURM) and Rajiv Awas Yojana (RAY) give special attention on `land tenure' and monetisation of land to promote equitable distribution of urban infrastructure. - Reproduced.
Keywords: Land reform